Regulatory barriers and entry in developing economies - John Bennett; Saul Estrin (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
We model entry by entrepreneurs into new markets in developing economies with regulatory barriers in the form of licence fees and bureaucratic delay. Because laissez faire leads to 'excessive' entry, a licence fee can increase welfare by discouraging entry. However, in the presence of a licence fee, bureaucratic delay creates a strategic opportunity, which can result in both greater entry by first movers and a higher steady-state number of firms. Delay also leads to speculation, with entrepreneurs taking out licences to obtain the option of immediate entry if they later observe the industry to be profitable enough.
Keywords: L50; O14; 330; Entry; Entry Barriers; Developing Economy; Markteintritt; Regulierung; Konzession; Wohlfahrtsanalyse; Theorie; Entwicklungsländer